A harmonic suppression method of variable frequency drive based on bacterial foraging algorithm. (2016) - Xiao, Dongming; Wang, Yong; He, Kuanfang; Li, Xuejun
A harmonic suppression method of variable frequency drive (VFD) based on bacterial foraging algorithm is developed in this study. The objective function to minimise total harmonic distortion (THD) with certain constraints is established. In order to solve a series of nonlinear transcendental equation, use bacterial foraging algorithm to get the optimal switching time in a certain frequency range and different load to determine the switching time of the inverter power devices. The simulation and experiment results show that the application of bacterial foraging algorithm can more effectively suppress the harmonic amplitude in theory, and the total harmonic distortion is smaller.